2017
DOI: 10.4028/www.scientific.net/kem.738.195
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Assessment of Structural Damping of Industrial Boiler Structure

Abstract: This article focuses on the estimation of a proper logarithmic damping decrement in industrial boilers when flue gases travel in the vertical direction. The structure for this type of facility is quite unified worldwide. The structural conception is rather simple, and the response to any static loading is predictable. Nevertheless, with regard to dynamics and damping, some specifics in the detailed solution make this system unique. For the purpose of this analysis, a Plexiglas scale model was prepared at a geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Based on the limitation of the provided shaking table test, the specimen was scaled to 1:2.35 ratio. The experimental model along with all of the applied ground motions was downscaled according to Buckingham Pi Theorem (Protivínský and Krejsa, 2016;Protivinsky et al, 2017) shown in Table I.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the limitation of the provided shaking table test, the specimen was scaled to 1:2.35 ratio. The experimental model along with all of the applied ground motions was downscaled according to Buckingham Pi Theorem (Protivínský and Krejsa, 2016;Protivinsky et al, 2017) shown in Table I.…”
Section: Methodsmentioning
confidence: 99%
“…The seismic design of cylindrical and rectangular tanks is recommended by various standards, their computational strategy is quite diverse, which in some cases leads to significantly different design forces [24 -26]. The best design codes for design solutions that deal with fluid tank systems are [27] API 650, 371 and 350.3, AWWA D100, AWWA D103, AWWA D110, AWWA D115, FEMMA 368, IBC 2000, ACI the Standards Association of New Zealand, NZSEE and Indian kóde IS 1893-1984 [28][29][30]. European Committee for Standardization set up European standard Eurocode 8 (2006) Design of structure for earthquake resistance -Part.…”
Section: Introductionmentioning
confidence: 99%
“…The fluid flows causes sloshing of free surface. The free liquid surface may experience different types of motion including simple planar, non-planar, rotational, irregular beating, symmetric, asymmetric, quasi-periodic and chaotic [18,19]. The type of motion is depended on the container shape and type of excitation.…”
Section: Introductionmentioning
confidence: 99%